Pengaruh Teknologi Informasi dan Integritas Profesionalitas Kerja pada Peningkatan Kinerja Seorang Auditor - Avionita Aprilia; Samsul Rosadi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The research paper focuses on the evaluation of the impact of information technology and professional integrity on auditor performance within the context of financial information reliability. The study defines auditing as the process of gathering and assessing evidence to determine the alignment of information with established criteria, emphasizing the need for competent and independent auditors. By employing a quantitative approach, the research aims to analyze the relationship between information technology, professional integrity, and auditor performance. The study was conducted from April to September 2024, involving auditors from a public accounting institution in Solo City. The findings highlight challenges faced by auditors, including instances of negligence, corruption, and bribery practices involving local government officials. These incidents underscore the significance of maintaining professional integrity, leveraging information technology effectively, and combating corruption to enhance auditor performance and ensure financial information credibility